Volcanic red soil in the tropical mountain region: landscape, parent materials, engineering characteristics, and its use on slope stability (case study: West Lampung, Sumatra, Indonesia) - Dicky Muslim; Prahara Iqbal; Nugroho Aji Satriyo (Geology, Ecology, and Landscapes)
The characterization of tropical mountain volcanic red soil in the tropical mountain region, West Lampung area, Sumatra, Indonesia concerning the landslide disaster has been carried out. The research methods used in this research are remote sensing methods, field geological mapping, petrographic analysis (thin section analysis), soil geotechnical analysis, soil geochemical analysis, slope stability analysis, and statistical analysis. The findings indicated that the study area’s volcanic red soil is distinguished by rolling hills with a V-shaped valley, a moderate to severe incline, and an elevation ranging from 850 to 1150 m above sea level. The soil is volcanic residual soil which resulted in wet tropics and from tuff layer and tuffaceous breccias in the felsic composition of the hydrothermal alteration environment. The soil of the study area has a reddish-brown color, and loose characteristic, and belongs to the type of very loose to solid high plasticity uniform inorganic sandy clayey silt. Based on saturated soil slope stability analysis, volcanic red soil has a stable to unstable category if forming a slope. The intrinsic factor that affects the stability of the slope is the percentage of clay content, electrical sensitivity, plasticity index, degree of saturation, and percentage of clay mineral content.